FUNCȚIILE FILOSOFIEI ȘI ROLUL EI ÎN VIAȚA PRACTICĂ ÎN CONCEPȚIA GÂNDITORILOR ROMÂNI DIN SEC.AL XX-LEA - Coandă, Svetlana (CEP USM, 2024)
The article analyzes the conceptions of Romanian thinkers: C.Rădulescu-Motru, L.Blaga, P.P.Negulescu, M.Florian, C.Noica with reference to the role of philosophy in practical life. Based on the analysis of reference works, comparison and synthesis, we came to the conclusion that these thinkers mentioned the importance of philosophy in the formation of personality according to ideals, a certain hierarchy of values, developing the critical spirit, will power, the ability to harmonize different points of view, freedom of thought, human dignity, etc. Philosophy ensures the spiritual continuity of generations, its role in practical life manifesting itself by being a source of activity goals and criteria of appreciation in accordance with authentic values.
THE FUNCTIONS OF PHILOSOPHY AND ITS ROLE IN PRACTICAL LIFE IN THE CONCEPTION OF ROMANIAN THINKERS OF THE 20TH CENTURY
Keywords: philosophical consciousness; activity ideals; philosophical tolerance; the value of philosophy; practical life